Fracture behavior and mechanism of highly fragmented steel cylindrical shell under explosive loading - Wang, Kang; Chen, Peng; Sun, Xingyun; Liu, Yufeng; Meng, Jiayu; Li, Xiaoyuan; Zheng, Xiongwei; Xiao, Chuan (Defence technology, 2024)
An in-depth understanding of the fracture behavior and mechanism of metallic shells under internal explosive loading can help develop material designs for warheads and regulate the quantity and mass distribution of the fragments formed. This study investigated the fragmentation performance of a new high-carbon silicon-manganese (HCSiMn) steel cylindrical shell through fragment recovery experiments. Compared with the conventional 45Cr steel shell, the number of small mass fragments produced by the HCSiMn steel shell was significantly increased with a scale parameter of 0.57 g fitted by the Weibull distribution model. The fragmentation process of the HCSiMn shell exhibited more brittle tensile fracture characteristics, with the microcrack damage zone on the outer surface being the direct cause of its high fragmentation. On the one hand, the doping of alloy elements resulted in grain refinement by forming metallographic structure of tempered sorbite, so that microscopic intergranular fracture reduces the characteristic mass of the fragments; on the other hand, the distribution of alloy carbides can exert a "pinning" effect on the substrate grains, causing more initial cracks to form and propagate along the brittle carbides, further improving the shell fragmentation. Although the killing power radius for light armored vehicles was slightly reduced by about 6%, the dense killing radius of HCSiMn steel projectile against personnel can be significantly increased by about 26% based on theoretical assessment. These results provided an experimental basis for high fragmentation warhead design, and to some extent, revealed the correlation mechanism between metallographic structure and shell fragmentation.